Thinking beyond the present: advocating continuity of practice of emergency remote teaching in Higher Education Institutions in Nigeria (2023)
The COVID-19 pandemic led to the disruption of education systems and the closure of schools all over the world. To ensure that teaching and learning continued during the pandemic, Higher Education Institutions (HEI) in Nigeria adopted Emergency Remote Teaching (ERT) and moved classes to online and distance education platforms. The expectation is that ERT will be an alternative to face-to-face teaching methods, which were the norm before the COVID-19 pandemic. In this paper, we argue in favour of HEIs continuing to utilize ERT rather than leaving remote teaching by both lecturers and students untapped. We will also provide justifications to support this ongoing use of ERT. We suggest that institutions should embrace a blended learning approach. This involves implementing an ERT contingency plan for potential future crises, integrating ERT as a mandatory component of academic staff professional development, enhancing the skills and readiness of academic and support staff for ERT, and formulating a strategy to address the challenges associated with ERT. We conclude that ERT presents a promising pedagogical approach that has the potential to bring about positive transformations in Nigerian higher education institutions.